PENGARUH PRODUK, HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE IPHONE DI KELURAHAN TALANG UBI UTARA KABUPATEN PALI - Salsabillah Saniyyah Qonitah; Diah Isnaini Asiati; Fitantina (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Teknologi Sumbawa, 2024)
This research aims to determine the influence of product, price and promotion on the decision to purchase an iPhone smartphone in Talang Ubi Utara Subdistrict, PALI Regency simultaneously and partially. This type of associative research, The sample used was 100 respondents taken using the purposive sampling method. The main data used is primary data using a questionnaire. The analysis technique uses multiple linear regression, F and t hypothesis testing and the coefficient of determination. The results of multiple linear regression research show that product quality, price and promotion have a positive influence on the decision to purchase iPhone smartphones among people in Talang Ubi Utara Subdistrict, PALI Regency. The results of simultaneous hypothesis testing show that there is a significant Customer Decisions. Specifically, there is a significant influence of Products on Customer Decisions, there is a significant influence of Price on Customer Decisions, and there is a significant influence of Promotion on Customer Decisions on Smartphone Purchase Decisions among the people in Talang Ubi Utara Village, PALI Regency. The results of the coefficient of determination show that the Product, Price and Promotion variables are able to contribute to the rise and fall of Purchasing Decisions by 62.9%,